2009
DOI: 10.1007/s00701-009-0480-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of foramen magnum dimensions and intracranial volume in pediatric Chiari I malformation

Abstract: The authors provide a simple, accurate and reproducible method of estimating foramen magnum area in the pediatric Chiari I group. The irregular shape of the foramen magnum is accentuated by developmental bony and soft tissue anomalies at the cranio-vertebral junction in Chiari malformation. Consequently, an individualized cross-sectional assessment of the foramen magnum in relation to the hindbrain tissue in the same plane is required to study the initiation and propagation of the Chiari I symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 22 publications
1
36
3
Order By: Relevance
“…Foramen magnum size appeared to be however evenly distributed between both groups; therefore, only the size of the Chiari I malformation had an influence on syrinx formation. This finding is in agreement with another study, which has not found a relationship between foramen magnum diameter and the incidence of Chiari I either [23]. Dufton et al [24] came to the conclusion that a wider foramen magnum diameter in Chiari I patients is associated with a greater tonsillar descent, which may explain why a larger foramen magnum diameter does not protect against cervical syrinx formation.…”
Section: Discussionsupporting
confidence: 81%
“…Foramen magnum size appeared to be however evenly distributed between both groups; therefore, only the size of the Chiari I malformation had an influence on syrinx formation. This finding is in agreement with another study, which has not found a relationship between foramen magnum diameter and the incidence of Chiari I either [23]. Dufton et al [24] came to the conclusion that a wider foramen magnum diameter in Chiari I patients is associated with a greater tonsillar descent, which may explain why a larger foramen magnum diameter does not protect against cervical syrinx formation.…”
Section: Discussionsupporting
confidence: 81%
“…The view generally accepted of CM pathogenesis is that the hindbrain develops normally after birth but later herniates into the spinal canal due to overcrowding of the posterior cranial fossa and dysplasia of the occipital somites of the mesodermal at the embryonic stage or the developmental lag of occipital somites (Schijman, 2004;Park et al, 2009;Furtado et al, 2010). SM is secondarily derived from the abnormal anatomy of the foramen magnum.…”
Section: Discussionmentioning
confidence: 99%
“…1,[17][18][19]33,34,47,50,52,54 Surgical treatment with posterior fossa decompression (PFD) is not universally successful, with failure of symptomatic resolution reported in up to a third of cases. 17,42,43,61 The pathogenesis of syringomyelia in CM-I (and other etiologies) remains unclear, which makes it difficult to develop improved treatments.…”
mentioning
confidence: 99%